Hafalan qur’an tak lagi sulit : 5 poin mutqin (mengaji bil ghoib tanpa kesalahan) - Jazuli, Muhammad Sulaiman (Maliki Interdisciplinary Journal, 2024)
It is no secret that there are some hufadz who do not have fluent memorization. Various methods are used, but none of them work. In this article, points will be explained so that we do not make mistakes in memorizing the Qur’an. What we all know is that mutqin is a reference or benchmark for measuring how strongly the memorization of the Qur’an is owned by hufadz. Everyone has a different way of strengthening memorization. However, the methods they use are not necessarily correct and relevant. There are difficult, easy, long-winded, or concise ways. Therefore, proper guidance is needed to achieve mutqin memorization. This includes knowledge of how to memorize the Qur’an properly and correctly. This is often trivial because some hufadz speculate that memorizing the Qur’an only needs to be read, memorized, and repeated. In fact, there are several points that can be added so that the speculation is much more complex. As the author, I want to convey the points that must be achieved during the memorization process. The hope is that we, as Hufadz, can feel the pleasure of having a complete memorization of the Qur’an.